Prevalence And Knowledge Of Hepatitis C Virus Infection Among Residents In Otukpo Town, Benue State, North Central Nigeria - Okoh, Ameh. M; Aremu, Olatunji; Suleiman, Ismail A (Journal of Current Biomedical Research, 2022)
Hepatitis C virus infection is one of the major causes of morbidity and mortality worldwide. Within the last decade, its sero-prevalence has been reported to be more than 170 million infections worldwide. The study determined the sero-prevalence and knowledge of Hepatitis C Virus infection in Otukpo, Benue State, North Central Nigeria A descriptive cross-sectional survey of the residents in Otukpo was carried out with the aid of pretested semi structured questionnaire. Consented respondents were also screened for Hepatitis C infection using the Anti-HCV rapid test strip. The associations between relevant variables were also determined. Hepatitis sero-prevalence rate within the study population was 2.8%. Most of the respondents that participated in the study were within the age bracket of 25 – 44 years 195 (51.6%). About fifty eight percent 226 (57.7%) were females and most of the respondents had formal education. Knowledge and awareness of Hepatitis C was poor. Only one third of the respondents had appreciable knowledge of Hepatitis C. Significant statistical association occurred only between gender (male and female) Hepatitis C outcome. The study showed Hepatitis C sero-prevalence rate was relatively high in the studied population. Their knowledge and practices to avoid Hepatitis C virus were also discovered to be very low.